2018
DOI: 10.15241/ctb.8.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Undergraduate Student Retention in STEM Majors: Career Development, Math Ability, and Demographics

Abstract: Despite efforts to boost mental health treatment-seeking behaviors by combat veterans, rates have improved relatively little since 2004. Previous work suggests that trust and confidence in the mental health community may be a significant factor. This study explored how professional titles may impact trust and confidence among active-duty U.S. Army soldiers (n = 32). Consistent with previous research, eight vignettes were used to solicit ordinal (ranked) trust and confidence scores for mental health professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The model accurately predicted 80% of the cases, thus providing some initial evidence that it is important to foster students' career‐related self‐efficacy to increase their odds of persistence in STEM. Furthermore, the finding that CSES scores positively predicted increased odds of persistence aligned with Belser et al's (2017, 2018) studies. Addressing students' career development such as their career‐related self‐efficacy or negative career thoughts is helpful to improving persistence outcomes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The model accurately predicted 80% of the cases, thus providing some initial evidence that it is important to foster students' career‐related self‐efficacy to increase their odds of persistence in STEM. Furthermore, the finding that CSES scores positively predicted increased odds of persistence aligned with Belser et al's (2017, 2018) studies. Addressing students' career development such as their career‐related self‐efficacy or negative career thoughts is helpful to improving persistence outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…Belser et al (2017) found that 1st‐year undergraduate students who declared a STEM major and participated in a STEM‐focused career planning course were 17.8 times more likely to stay in a STEM major for a 2nd year. Belser et al (2018) also predicted retention of students in a STEM career planning course using the Career Thoughts Inventory. As students' negative career thoughts decreased, their odds of 2nd‐year retention increased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, spatial thinking skills vary both at a group level and at the individual level. There are cases where group differences are of concern to the instructor, for example, in consideration of male–female differences in entry and retention rates in STEM disciplines (Belser et al 2018 ; Chen 2013 ; Sithole et al 2017 ). Instructors are also concerned with individual differences in aptitudes; for example, students vary in their spatial and verbal abilities and some students are good at spatial tasks and some are good at verbal tasks.…”
Section: Characteristics Of Spatial Thinkingmentioning
confidence: 99%
“…The primary intervention of the program is the STEM-focused career planning course, which aims to help students who have not yet solidified their undergraduate majors but have at least a minimal interest in pursuing a career in STEM. Prior research on this particular course has established its efficacy in helping students become more solidified in their decisions about majors and careers (Belser, Prescod, Daire, Dagley, & Young, 2017;Belser, Prescod, Daire, Dagley, & Young, 2018;Belser, Shillingford, Daire, Prescod, & Dagley, 2018;Prescod, Daire, Young, Dagley, Georgiopoulos, 2018).…”
Section: The Living Learning Communitymentioning
confidence: 99%